We know they train, but what do they do? Implications for coaches working with adolescent rugby union players - Phibbs, P. J.; Jones, B.; Roe, G. A. B.; Read, D. B.; Darrall-Jones, J.; Weakley, J. J. S.; Till, K. (International Journal of Sports Science & Coaching, 2017)
Limited information is available regarding the training loads of adolescent rugby union players. One-hundred and seventy male players (age 16.1±1.0 years) were recruited from 10 teams representing two age categories (under-16 and under-18) and three playing standards (school, club and academy). Global positioning systems, accelerometers, heart rate and session-rating of perceived exertion (s-RPE) methods were used to quantify mean session training loads. Session demands differed between age categories and playing standards. Under-18 academy players were exposed to the highest session training loads in terms of s-RPE (236±42 AU), total distance (4176±433m), high speed running (1270±288m) and PlayerLoad™ (424±56 AU). Schools players had the lowest session training loads in both respective age categories. Training loads and intensities increased with age and playing standard. Individual monitoring of training load is key to enable coaches to maximise player development and minimise injury risk. FROM AUTHOR